2020
DOI: 10.1093/toxsci/kfaa098
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical Safety Assessment of AMG 553, an Investigational Chimeric Antigen Receptor T-Cell Therapy for the Treatment of Acute Myeloid Leukemia

Abstract: FMS-like tyrosine kinase 3 (FLT3), a tyrosine-protein kinase involved in hematopoiesis, is detectable on the cell surface of approximately 80% of leukemia isolates from adult patients with acute myeloid leukemia (AML). AMG 553 is an investigational chimeric antigen receptor (CAR) T-cell immunotherapy for the treatment of AML. FLT3 expression analysis and in vitro and in vivo studies were leveraged to evaluate the nonclinical safety of AMG 553. Cynomolgus monkeys administered autologous anti-FLT3 CAR T cells de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Previously, a phase 1 clinical trial revealed no grade 3 or above adverse events related to NKG2D CAR T cell therapy in patients with relapsed/refractory AML [43], indicating that it is safe targeting NKG2DLs in AML patients. Clinical data regarding the safety of FLT3-CAR T cells are currently not available, but a nonclinical safety assessment demonstrated that FLT3-CAR T cells only affect a small percentage of normal haematopoietic stem and progenitor cells [44], which is in agreement with our findings. In contrast, other studies have reported that FLT3-CAR T cells do not deplete HSCs and that HSC differentiation is preserved [17].…”
Section: Discussionsupporting
confidence: 91%
“…Previously, a phase 1 clinical trial revealed no grade 3 or above adverse events related to NKG2D CAR T cell therapy in patients with relapsed/refractory AML [43], indicating that it is safe targeting NKG2DLs in AML patients. Clinical data regarding the safety of FLT3-CAR T cells are currently not available, but a nonclinical safety assessment demonstrated that FLT3-CAR T cells only affect a small percentage of normal haematopoietic stem and progenitor cells [44], which is in agreement with our findings. In contrast, other studies have reported that FLT3-CAR T cells do not deplete HSCs and that HSC differentiation is preserved [17].…”
Section: Discussionsupporting
confidence: 91%
“…We demonstrate potent in vitro and in vivo anti-leukemia efficacy against FLT3-mutant AML and KMT2A-R ALL cell lines, as well as robust FLT3CARTmediated eradication of leukemia in vivo in several PDX models of pediatric or young adult FLT3-mutant AML, FLT3 wild-type AML, and KMT2A-R ALL. Consistent with other studies of FLT3-directed CAR T cell immunotherapies, [38][39][40][41][42] our FLT3CART showed excellent activity against FLT3-ITD AML via in vitro cytokine production and viability metrics, as well as in vivo curative effects and long-term animal survival. We were intrigued to discover that flow cytometric FLT3 surface antigen site density was not overtly different in our tested FLT3-mutant vs non-mutant AML cell lines and PDX models and that FLT3CART also had strong (albeit less complete) activity against FLT3 wild-type AML.…”
Section: Discussionsupporting
confidence: 88%
“… An overview of different anti-FLT3 CAR T-cells developed to date. ( A ) A second-generation CAR with CD28 as co-stimulatory domain [ 30 , 31 , 32 ]. ( B ) A second-generation CAR with 4-1BB as co-stimulatory domain [ 30 , 33 ].…”
Section: Configuration Of Chimeric Antigen Receptorsmentioning
confidence: 99%
“…Karbowski et al present the only study using cynomolgus monkeys to demonstrate tolerability, safety, and dose-dependent efficacy vs. toxicity [ 32 ]. Karbowski et al sought to mimic the human environment as closely as possible to improve prediction of clinical performance and safety of their anti-FLT3 CAR T-cell therapy [ 32 ]. They specifically examined the monkeys for FLT3 expression in tissues that were previously documented to express the FLT3 protein.…”
Section: In Vivo Assessment Of Efficacy and Safety Of Anti-flt3 Car T...mentioning
confidence: 99%
See 1 more Smart Citation